THE INFLUENCE OF SERVICE QUALITY IN THE HIGHER EDUCATION PERFORMANCE MODEL ON STUDENT SATISFACTION WITH INFORMATION QUALITY AS A MODERATING VARIABLE IN ACCOUNTING STUDENTS AT PRIMA INDONESIA UNIVERSITY - Fikaria Br Tarigan; Tony Wijaya (ADISAM Publisher, 2024)
This research aims to explain the influence of service quality on student satisfaction with information quality as a moderating variable in accounting students at Prima Indonesia University. This research is a causal associative study using a quantitative approach. The research subjects are undergraduate students majoring in Accounting at Prima Indonesia University. The population in this study consisted of 1863 students. The sample size for this study was 330 respondents, selected using purposive sampling technique. The research instrument used a closed-ended questionnaire distributed to the respondents. Data analysis was conducted using Structural Equation Modeling Partial Least Square (PLS) version 3.2.9. The results of this study are as follows: (1).Service quality has a positive and significant influence on student satisfaction (p < 0.000). (2).Information quality moderates the influence of service quality on student satisfaction (p < 0.014). From these results, it can be concluded that information quality can create better student satisfaction. Therefore, to maximize student satisfaction, universities need to pay attention to both service quality and the quality of information provided to students